Democracy versus liberty ?: the faith of a liberal heretic - De Madariaga ,Salvador (London, 1958)
This booklet is in fact a translation of the second part of a political essay author published in French under the title of De l'Angoisse a la Liberté. His aim was to endeavour to outline the main principles a democracy should uphold and the new methods it should apply to remain liberal. True to type, my British liberal friends brushed aside the first part-principles-to concentrate on the second-methods. They are, however, open-minded enough to let me put forward a brief statement of my liberal principles by way of an introduction to my suggestions on methods.
Keywords: Democracy